HASIL BELAJAR KOGNITIF BIOLOGI SISWA PUTRA DAN PUTRI KELAS XI IPA SMA DI KOTA BANJARMASIN PADA STRATEGI PEMBELAJARAN PQ4R DIINTEGRASIKAN PETA KONSEP - Ramdiah, Siti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Advancement of science and technology requires people to be able to compete in sustaining life. Therefore, human resource through education can be improved and developed to be a quality resource. It can be seen from the achievement of learning achieved by students. Learning is good, when most students acquire learning outcomes as expected. But in fact, these efforts have not been done in the field with the maximum. This quasi-experimental study aimed at revealing the influence of the learning strategy PQ4R integrated concept maps on the biology of cognitive learning outcomes, the influence of gender on cognitive learning outcomes, as well as the interaction effect PQ4R integrated learning strategy map concept and gender on cognitive learning outcomes of students. The design of this study pretest-posttest Non-Equivalent Control Group Design ". Data collection dependent variable through the essay test. Cognitive learning outcomes assessment refers to Hart (1994). Data were analyzed with Anacova. The results showed that the learning strategy affects the outcome of cognitive learning. Gender differences have a significant influence on the cognitive achievement of students in class XI science high school in the city of Banjarmasin. Furthermore, there was no interaction effect of learning strategy and gender on cognitive learning outcomes of students in class XI science high school in the city of Banjarmasin.Keywords: PQ4R, Concept maps, cognitive learning, son, daughter